(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Evaluating the Effectiveness of Promotional Strategies in Enhancing Tourism in Madhya Pradesh: Current Practices and Future Prospects Sarthak Chourasia Dr. Avinash Vikram Dr. Lokeshver Singh Jodhana Abstract:This research paper aims to evaluate and synthesize existing literature on the promotional strategies adopted in the tourism industry of Madhya Pradesh, India. The study focuses on assessing the impact of various marketing campaigns, including digital and traditional advertising techniques, cultural promotions, public-private partnerships, and supportive government policies. By analyzing these initiatives, the research highlights the role of branding, infrastructure development, and innovative promotional tools in positioning Madhya Pradesh as a competitive tourism destination in India.